The Relationship between Stock Market and Economic Growth in Nigeria: VAR Granger Approach - Yusuf Adebola Bako; Najeem Ayodeji Isiaka (International Journal of Economics, Social Science, Entrepreneurship and Technology (IJESET), 2022)
This study investigated the relationship between stock market and economic growth in Nigeria, covers the period of 20years between 2000 and 2019. Data on market capitalization, all share indexes, value of shares, Treasury bill rate and inflation were considered and gathered from CBN Statistical Bulletin, 2019. Ordinary Least Square method was employed and data were analyzed with the aid of Eview 09. The result revealed that market capitalization proxied for stock market have a positive relationship and statistically significant to influence economic growth at 82% magnitude. However, Treasury bill rate, value of shares, all share indexes and inflation rate have no significant impact on economic growth. Also, VAR-Granger causality revealed that there is no long-run relationship between the variables in the model due to the scope of the data. It was further shows that market capitalization, treasury bill rate , value of shares, all share indexes and inflation rate do not granger cause or have causal relationship with economic growth except GDP that influences the treasury bill rate and value of shares. Based on the findings, it was concluded that if stock market is well managed and improve on their activities, it contributes significantly to the Nigerian economy. Therefore, the study recommends that monetary authority should implement a policy that will boost stock market and increase the Treasury bill rate for attracting more investors.